Proteomic analysis of barley cell nuclei purified by flow sorting - Petrovská, Beáta; Jeřábková, Hana; Chamrád, Ivo; Vrána, Jan; Lenobel, René; Uřinovská, Jana; Sebela, Marek; Doležel, Jaroslav (Cytogenetic and genome research, 2014)
Many proteins are present in the nucleus; some are involved with its structural and functional organization, some with gene expression, and some with cell division. The plant nuclear proteome has not been well explored. Its characterization requires extraction methods which minimize both the artifactual alteration of the proteins and the extent of contamination with non-nuclear proteins. The conventional multi-step fractionation procedure is both laborious and prone to contamination. Here, we describe a single-step method based on flow sorting. The method allows the separation of G1, S and G2 phase nuclei and minimizes the risk of contamination by non-nuclear proteins. Preliminary results obtained using G1 phase cell nuclei from barley root tips indicate that flow sorting coupled with a protein/peptide separation and mass spectrometry will permit a comprehensive characterization of the plant nuclear proteome.
Keywords: Hordeum; proteom; proteomika; interfáze; průtoková cytometrie; Proteomics; Proteome; buněčné jádro; Cell Nucleus; Plant Proteins; ječmen (rod); Flow Cytometry; rostlinné proteiny; Interphase